Central Bank Independence, Transparency and Accountability Indexes: a Survey - Dumiter Florin Cornel (Timisoara Journal of Economics and Business, 2014)
Recently, the remarkable trend upon central bank independence and the efficient monetary policy were seriously highlighted in the monetary economics field. Starting from 1990s’ central bank independence was at the core of policy making and central banking problems, because of the widespread economical, political, personal and budgetary autonomy of the central bank. Nowadays, we can observe an increasing trend upon central bank transparency, for evaluating more accurate the central bank’s performances by the wide public, mass-media and financial markets. Consequently, a central bank must encompass a high degree of accountability and responsibility, because of the final liability in case of failure. In this paper we present, analyze and assess the construction of the most important indices regarding central bank independence, transparency and accountability in a chronological manner, presenting also the advantages and disadvantages of these indices related to actual practices of central banks. Moreover, we analyze the analytical results of the empirical testing of these indices with a considerable impact upon the developed and developing country group. In regard with the empirical results of different authors, we suggest the importance and the necessity for constructing an aggregate index for measuring central bank independence, transparency and accountability, based on de jure stipulations and the actual practices of the central banks.